2022
DOI: 10.1002/lary.30364
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Reality Enhanced Otolaryngology Case‐Based Learning: A Randomized Educational Study

Abstract: Introduction The COVID‐19 pandemic has caused unprecedented disruptions to medical education. Education in medical specialties, such as otolaryngology faces multiple challenges, including reduced bedside and “hands‐on” training opportunities at all levels. Educators are turning to technological advancements to deliver effective remote medical education. This study investigated the value of enhancing traditional remote case‐based teaching with the HoloLens2™. Methods We present a randomized educational design s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Particularly, when used for medical students, following proper educational strategies, using experienced mentors, and extensive content with a wide variety of features, VR-based education can arguably be the method of choice for teaching during COVID-19 limitations (38, 51). Positive outcomes, bene ts for medical students, and professors, facilitation of the content transition, and improvement of the educational process, with VR-enhanced learning, are some of the most mentioned conclusions in the entered studies (29,35,42,43) Furthermore, increased students' engagement/participation, enjoyment, motivation, and focus were also frequently observed (28,32,41,43).…”
Section: Effectivenessmentioning
confidence: 97%
See 2 more Smart Citations
“…Particularly, when used for medical students, following proper educational strategies, using experienced mentors, and extensive content with a wide variety of features, VR-based education can arguably be the method of choice for teaching during COVID-19 limitations (38, 51). Positive outcomes, bene ts for medical students, and professors, facilitation of the content transition, and improvement of the educational process, with VR-enhanced learning, are some of the most mentioned conclusions in the entered studies (29,35,42,43) Furthermore, increased students' engagement/participation, enjoyment, motivation, and focus were also frequently observed (28,32,41,43).…”
Section: Effectivenessmentioning
confidence: 97%
“…Collaboration and learning in groups to solve VR-based problems is a common motivator. More importantly, the ability for users or students to explore the virtual environments either alone or with the help of other classmates or instructors not only increases motivation but also increases the enjoyment (41,43).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…
It was our pleasure to read the article by Malik et al 1 who investigated the implementation of mixed reality (MR) in otolaryngology education. It was demonstrated that this teaching modality was beneficial for medical students' performance, and it was also positively perceived.
…”
mentioning
confidence: 99%
“…We thank Chytas et al for the response to our article and highlighting some important points of consideration going forward. 1,2 The technological ecosystem of immersive technologies in which Mixed reality (MR) and Augmented reality (AR) exist is rapidly progressing. 3 With this, definitions and descriptions of novel technologies often evolve and are at constant risk of becoming outdated and misunderstood.…”
mentioning
confidence: 99%